5=3(x+7)-2x

Simple and best practice solution for 5=3(x+7)-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=3(x+7)-2x equation:



5=3(x+7)-2x
We move all terms to the left:
5-(3(x+7)-2x)=0
We calculate terms in parentheses: -(3(x+7)-2x), so:
3(x+7)-2x
We add all the numbers together, and all the variables
-2x+3(x+7)
We multiply parentheses
-2x+3x+21
We add all the numbers together, and all the variables
x+21
Back to the equation:
-(x+21)
We get rid of parentheses
-x-21+5=0
We add all the numbers together, and all the variables
-1x-16=0
We move all terms containing x to the left, all other terms to the right
-x=16
x=16/-1
x=-16

See similar equations:

| 5w+20=7w-4 | | 15+-4x=10x+45 | | -(3/2y-60+2=(7/y-3) | | 7x=310=x | | -(3/(2y-60)+2=(7/(y-3)) | | 101,5=2,5x+5 | | 4(3w=6)=8w= | | -3(2t+7=-33t= | | 2x^2-17x=84 | | s=59*10-43 | | 4x-3=3+5x | | 2323227xxxxxx= | | 3(f-10)=-24f= | | 2x+-3(x+-1)=17 | | 5e+4=59+143 | | X+2x+x=5x | | (4w+6)(4-w)=0 | | 5x+15=9x+18=3x+12=15x | | 4+7x=55 | | C^2-3c-5=0 | | -10(s+5)=25s= | | -(c-8)=0c= | | t2+6t=16 | | 4n+3=149 | | 4x+(2x+6)=90 | | x-3/8=3x+2 | | 7y-46=4•y-4 | | 0=x^2-2x=24 | | 52x4=208 | | 3(t+3)=3t= | | u^2-50u+100=0 | | y=0.7(-8)+13 |

Equations solver categories